Development of Climate-Related Risk Maps and Adaptation Plans (Climate Smart MAP) for Rice Production in Vietnam’s Mekong River Delta - Hong Son, Nguyen; Tan Yen, Bui; Sebastian, Leocadio S. (2018)
The El Niño-Southern Oscillation (ENSO) in 2016 adversely affected Vietnam particularly the Mekong River Delta (MRD), where more than 90% of the country’s rice export is produced annually. To address this and prepare for future climate risks, the Department of Crop Production (DCP), Ministry of Agriculture and Rural Development (MARD) of Vietnam, and CGIAR Research Program on Climate Change, Agriculture and Food Security in Southeast Asia (CCAFS SEA) collaborated to develop and test climate-related risks maps and adaptation plans (Climate Smart MAP/CS MAP) for recognizing climate-related risks, identifying potentially affected areas and developing regional and provincial adaptation plans for rice production. Changing rice-based cropping systems and sowing/transplanting calendars were common adaptive options proposed by provinces. CS MAP is now being developed at different stages for 13 provinces in the MRD. Some provinces are implementing the adopted measures and developing the corresponding monitoring and reporting tools.